Promoting the development of research competency through active methodologies in b-learning - José Sánchez-Santamaría; Sonia Morales Calvo (Universidad de La Rioja, 2014)
This article analyses the main findings of a study on the use of active methodologies for competency development in a B-learning, in particular, research professional competency in Social Education. To do this, a reflection on Competency-Based Education is proceed, in connection with active methodologies and B-learning; secondly, a delineation and characterization of the Social Educator's competence profile is carried out; Thirdly, the educational context in which development experience is addressed; fourth, the methodology of study is showed; fifth, the results on the degree of usefulness: perceived competence development and satisfaction with the development of the subject are analyzed. And finally, it describes the conclusions that, as a prospective, we help guide the further processes of reflection and action in teaching. The results highlight the important role of active methodologies in B-learning in the work of general, lateral and cognitive competencies, like allowing a teaching-learning process more continuous, progressive and personalized.